Seasoning ingredients in a medium–fat diet regulate lipid metabolism in peripheral tissues via the hypothalamic–pituitary axis in growing rats. Issue 3 (4th March 2018) - Tanaka, Mitsuru; Yasuoka, Akihito; Yoshinuma, Haruka; Saito, Yoshikazu; Asakura, Tomiko; Tanabe, Soichi
Abstract: We fed rats noodle (N) -diet containing 30 wt.% instant noodle with a 26% fat-to-energy ratio for 30 days (N-group). Compared with rats that were fed the same amount of nutrients (C-group), the N-group showed lower liver triacylglycerol levels and higher fecal cholesterol levels. We then analyzed transcriptome of the hypothalamic–pituitary (HP), the liver and the white adipose tissue (WAT). Thyroid stimulating hormone (Tshb), and its partner, glycoprotein hormone genes were up-regulated in the HP of N-group. Sterol regulatory element binding transcription factors were activated in the liver of N-group, while an up-regulation of the angiogenic signal occurred in the WAT of N-group. N-group showed higher urine noradrenaline (NA) level suggesting that these tissue signals are regulated by NA and Tshb. The N-diet contains 0.326 wt.% glutamate, 0.00236 wt.% 6-shogaol and Maillard reaction products. Our results suggest that these ingredients may affect lipid homeostasis via the HP axis. Abstract: : Summary of physiological pathway accelerated by seasoning ingredients in instant noodle.